The water supply of England and Wales the geology, underground circulation, surface distribution, and statistics - De Rance, Charles E. (Edward Stanford, 1882)
The author tried to show the character and quantity of the water then supplied to every town and urban sanitary authority in England and Wales, and, taking into account principal geological formations and rainfall, to estimate the volume of water available and the quantity required for human consumption in each group of river basins.